1998
DOI: 10.1089/vim.1998.11.167
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T-Lymphocyte Responses to HIV-1 Reverse Transcriptase (Review)

Abstract: Cytotoxic T lymphocytes (CTL) play an important role in the control of human immunodeficiency virus (HIV) infection. CTL responses have been demonstrated for most of the HIV gene products, predominantly gag, pol, and env-encoded proteins, and also for the regulatory proteins Nef, Tat, Vif, or Rev. The HIV-1 reverse transcriptase (RT), which derives from expression of the pol gene, is an important target of cellular immune responses in infected individuals. More than 40 different peptides containing RT-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Finally, this synthetic gene represents a valid immunogen, whose intracellular processing can be altered and which can be incorporated into any nonreplicating viral vector system (or combination thereof) to optimize host immunity. As increasing numbers of Pol T-cell epitopes are identified in seropositive human subjects (26,35), it becomes apparent that the inclusion of a pol component in an HIV vaccine will improve the breadth of the cellular immune responses and will increase the likelihood of establishing protection against an HIV infection. …”
Section: Vol 76 2002mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this synthetic gene represents a valid immunogen, whose intracellular processing can be altered and which can be incorporated into any nonreplicating viral vector system (or combination thereof) to optimize host immunity. As increasing numbers of Pol T-cell epitopes are identified in seropositive human subjects (26,35), it becomes apparent that the inclusion of a pol component in an HIV vaccine will improve the breadth of the cellular immune responses and will increase the likelihood of establishing protection against an HIV infection. …”
Section: Vol 76 2002mentioning
confidence: 99%
“…As the product of the largest structural gene in the HIV genome, it contains many T-cell epitopes. In fact, Pol-specific T-cell responses have been identified in infected HIV-1 patients with very high incidence (21), and over 60 CTL epitopes have been reported thus far (26,35). For these reasons, Pol would be integral to a vaccine that is capable of inducing potent, broad cellular immunity against HIV.…”
mentioning
confidence: 99%
“…Strong CTL responses are maintained in long-term nonprogressors and these responses correlate with decrease in viral load [51-55]. It has been shown that transmitting mothers have larger numbers of CTL escape variants as compared to non-transmitting mothers [56], emphasizing that CTL escape variants may become a part of circulating virus that influences vertical transmission [56,57]. Several regions in the RT gene have been shown to elicit strong CTL responses during HIV-1 infection.…”
Section: Resultsmentioning
confidence: 99%
“…3 The reverse transcriptase (RT) protein of HIV-1 is an important target of CTL responses in infected individuals, 4 and more than 40 different RT-specific CTL epitopes have been identified. 4 The RT enzyme is also a target for most approved antiretroviral therapies, 5 and similar to CTL evasion, selection for genetic mutations in HIV-1 RT decreases the susceptibility to these antiretroviral therapies.…”
mentioning
confidence: 99%
“…3 The reverse transcriptase (RT) protein of HIV-1 is an important target of CTL responses in infected individuals, 4 and more than 40 different RT-specific CTL epitopes have been identified. 4 The RT enzyme is also a target for most approved antiretroviral therapies, 5 and similar to CTL evasion, selection for genetic mutations in HIV-1 RT decreases the susceptibility to these antiretroviral therapies. 5 Understanding the antigenicity, immunogenicity, and evolution of CTL epitopes that incorporate antiretroviral (ART) drug resistance mutations (DRM) is perhaps a first step toward developing immune strategies against the emergence and transmission of drug-resistant HIV strains.…”
mentioning
confidence: 99%